Morphology, arrangement and classification of sensilla on the apical segment of labium in Peiratinae (Hemiptera: Heteroptera: Reduviidae) - Brożek, Jolanta; Chłond, Dominik (Zootaxa, 2010)
The present paper describes sensory structures on the apical segment of the labium in representatives of the subfamily Peiratinae (Heteroptera: Reduviidae), using the scanning electron microscope. The study is based on dry material representing 19 species and 16 genera. Within Peiratinae thirteen morphologically distinct types of sensilla were identified. Among them were four new types of sensilla (porous placodea sensillum [PPLS], multilobate sensillum [MS], domeelongated sensillum [UDES], and pit peg sensillum type 2 [NPPS2]) were found. Mechanosensilla are evenly distributed on the surface of the labium and form a characteristic pattern in various species. The main characters of the third visible (apical) segment of the labium are: presence of different sized sensilla of the chaetica type 1, 2, and 3; trichodea sensilla (TS); campaniform sensilla (CS); and various types of nonporous pit peg sensilla (NPPS1, NPPS2, and NPPS3). Distally on the apical segment of the labium dome-elongated sensilla (UDES) there are a characteristic arrangements, described as (3+3) and (1+2). Chemical sensilla are grouped on the tip of the labium. The position, number, and types of chemical sensilla on this area are very similar in all studied species.